Developing self-confidence in young writers - Bowkett , Steve (London : Bloomsbury, 2017)
One of the key inhibitors to children's development in writing is 'the fear of the blank page', coupled with the perceived inability to generate and properly structure ideas. The pressures children face in mastering the technicalities of writing can often exacerbate these difficulties. While spelling, punctuation and grammar are ultimately very important for clarity of communication, children can often become overwhelmed as they try to 'get everything right' at the first attempt. 'Developing Self-Confidence in Young Writers' tackles these issues head on.
Includes bibliography and index.
Keywords: English language -- Composition and exercises; Self-confidence.; Self-esteem.